(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saputra TI, Roberdi, Nugroho YA, Artutiningsih W, Purba OS, Maryanto SD, Yono D, Utomo C, Liwang T. 2021. The development of unlabeled probes-high resolution melting (UP-HRM) marker on SAD, IAA27 and ACC genes of oil palm. Biodiversitas 22: 3356-3362. The unlabeled probes-high resolution melting (UP-HRM) marker is a useful tool for detecting of single nucleotide polymorphisms (SNPs). The objectives of this study were to develop UP-HRM markers to differentiate specific SNPs patterns on oil palm. The marker was developed and tested with Elaeis guineensis (Eg), Elaeis oleifera (Eo), Eo x Eg (hybrid), and was validated with 53 individuals of BC1F1 populations ((Eo x Eg) x Eg). Four UP-HRM markers were developed based on 2 SNPs in the stearoyl-acyl-carrier-protein 9-desaturase (EgSAD), 1 SNP in the auxin-responsive protein IAA27-like (EgIAA27), and 1 SNP in the 1-amino cyclopropane-1-carboxylate oxidase (EgACC) genes. The SNP discovery result showed that Eg was represented a reference homozygote genotype, while Eo was represented as an alternative homozygote genotype and the Eo x Eg hybrid was represented as a heterozygote genotype in all genes. The typical UP-HRM melt curve graph was successfully generated. This result was consistent with each genotype model for all four markers. The UP-HRM markers can distinguish each genotype according to the single-pass sequencing results. Furthermore, dendrogram analysis on validation divided 53 BC1F1 samples into three cluster groups.